The impact of the stock market on liquidity and economic growth: Evidence of volatile market - Collin Chikwira; Iqbal Mohammed Jahed (Economies, 2023)
Stock markets serve as a conduit for money and liquidity, which are necessary for economic growth and stability. This study aimed to determine whether stock market impacts are communicated in an economically unstable environment, characterised by volatility, high inflation rates, and political instability. The research used a time series Vector Autoregressive model (VAR) with quarterly data from between 2013 and 2022. The study revealed that there is a positive statistically significant association between the stock market and economic growth at the 10% level. On the other hand, the stock market liquidity has no major influence on Zimbabwe's economic development. As a result, the study advises policymakers to evaluate the rules regulating the stock market carefully and to relax some of the requirements for firms to be listed on the stock exchange. The stock market will become more liquid as a result of this because it will draw more internal and external businesses to being listed. The ZSE should also develop a framework for the gradual implementation of the commodity derivatives exchange as Zimbabwe's substantial mineral reserves and robust agriculture may bring significant income to the country's economy.
Keywords: 330; stock exchange; liquidity; economic growth